Fermentation Kinetics and Gene Expression Patterns in Adenosine Biosynthesis by Bacillus subtilis - Gengxuan Yan; Haoqiong Wu; Shumei Zhang; Chunyan Liu; Yuan Tian; Chong Yu (Applied Sciences)
Adenosine holds significant application value in the fields of food additives and pharmaceutical intermediate synthesis. Engineering strains to enhance their efficiency in utilizing fermentation substrates is considered an effective strategy for improving production yield. However, modifications to adenosine-producing strains remain challenging due to the complex physiological and metabolic regulation governing adenosine biosynthesis. In this study, the molecular regulatory mechanisms of adenosine biosynthesis in a high-yielding Bacillus subtilis strain were analyzed through transcriptome sequencing. Under conditions in which an additional 10 g/L glutamine and 6 g/L hypoxanthine were supplemented at 48 h of cultivation to promote adenosine synthesis, a total of 105 significantly differentially expressed genes (69 downregulated and 36 upregulated) were identified, with key genes related to adenosine biosynthesis primarily concentrated in the downstream purine metabolic pathway. Notably, core biosynthetic genes including purD, guaC, purH, and purN showed significant downregulation in the high-yielding strain, suggesting that adenosine accumulation might inhibit related gene expression through negative feedback mechanisms. Fermentation kinetic analysis revealed that biomass reached its peak at 48 h (OD600 = 0.82), with a glucose consumption rate of 73.28% at this stage. Gene expression pattern analysis demonstrated that purD, guaC, purH, and purN maintained relatively stable expression levels during fermentation. However, the exogenous supplementation of inosine (6 g/L) and glutamine (10 g/L) induced significant inhibition of their expression—a trend paralleling that observed with exogenous adenosine addition. This research elucidates key regulatory nodes in the adenosine biosynthesis of Bacillus subtilis and provides theoretical support and candidate targets for the targeted modification of industrial strains through metabolic engineering strategies.